KEGIATAN "CREATIVE WRITING" UNTUK MENUMBUHKAN SEMANGAT LITERASI PADA ANAK-ANAK PANTI ASUHAN ARIA PUTRA CIPUTAT, TANGERANG SELATAN - Setiana Sri Wahyuni Sitepu; Linda Maisari; Siti Latifatul Rosidah (PENGABDIAN SOSIAL, 2023)
ABSTRACT Community service is the implementation of the practice of science, technology and arts and culture directly to the community institutionally through scientific methodology as the dissemination of the Tri Dharma of Higher Education and a noble responsibility in efforts to develop community capabilities, so as to accelerate the rate of growth in achieving national development goals. of the Tri Dharma pillar of Higher Education is Community Service which is carried out by lecturers and students. In this regard, lecturers and students from the English Literature study program at Pamulang University hold community service activities to apply the knowledge they have obtained from the Higher Education where they study knowledge. Therefore, lecturers and students will visit the Aria Putra Foundation to provide tips and directions for creative writing Keywords: . : Creative Writing, Literacy